A aprovação da Lei do Divórcio no Brasil : os debates e os embates por meio das revistas Manchete e Veja (1975-1977) - Quissini, Lauren Cavichioli (2022)
Although discussions on the divorce theme in Brazil have been present since at least the 19th century and have been intensified mainly between the 1950s, 1960s and 1970s, it was with the manifestations of the politician Nelson de Souza Carneiro that they gained concreteness. This research aims to analyze the speeches about the approval of Law 6.515/1977, known as the Divorce Law or Carneiro Law, sanctioned on December 26, 1977, by General-President Ernesto Geisel. In order to do so, the investigation highlights the years from 1975 to 1977, contextualizing the entire process that culminated in the approval of the law, since, first, the Senate considered the Proposed Amendment to the Constitution (PEC) 5/1975, by Senator Nelson Carneiro. Even having reached a majority in Congress, the proposal that opened the possibility for a couple to divorce did not win two-thirds of the votes necessary for its implementation at that time. The sources of information for this study derive from the magazines Manchete (which was in circulation between 1952 and 2000) and Veja (in circulation since 1968). With intense circulation and popularity among the Brazilian middle class, in the period, both gave considerable visibility to the divorce theme, amplifying, in their reports, debates and clashes that allowed identifying the discursive tendencies involved in the subject. Although the issue of divorce is not new, there are few works in the area of History relevant to the theme, especially with regard to the time frame traced. For the development of the research, the methodology of Discourse Analysis was used, investigating the positions of the two magazines and the way in which the debates on the cause of divorce between 1975 and 1977 were narrated. the approval of the Divorce Law in Brazil was inserted in the context of cultural, social and political transformations of the 20th century, which had repercussions on the revision of individual freedoms, especially in decisions related to the problems of families and couples. In the midst of a repressive military dictatorship, the Divorce Law legalized family reorganization, putting an end to difficult-to-resolve issues. At the same time, it displeased the Roman Catholic Church and supporters of its dogmas, among them, religious and political faithful. In addition to these, the divorce issue also displeased the civil Catholic movement Tradition, Family and Property (TFP) and some religious from The Church of Jesus Christ of Latter-day Saints (the Mormons), covered by the magazines Manchete and Veja in the course of the research.